The Realization of Leech Politeness Maxims Between the Host and His Guests’ Interaction in Jimmy Kimel Talk Show (Universitas Negeri Semarang, 2021)
This study is conducted to determine the realization of the politeness maxim using Leech’s (2014) theory of politeness on Jimmy Kimmel Talk show. There are two categories of politeness maxims namely pos-politeness maxim and neg-politeness maxim. Additionally, pos-politeness maxims consist of generosity, approbation, obligation S to O, agreement, and sympathy. Meanwhile, neg-politeness maxims consist of tact, modesty, obligation O to S, opinion reticence, and feeling reticence. This study employed a descriptive qualitative method in the form of pragmatic analysis to examine four episodes from the utterances between the host and his guest stars’ interactions. The classifications of utterances were analyzed and classified based on (Bogdan & Biklen, 2007). The findings of this study show that the host and his guest stars employ all pos-politeness and neg-politeness maxims during their interactions. Both the host and his guest stars employed tact (28.63%), opinion reticence (17.34%), agreement (14.54%), generosity (14.11%), approbation (9.27%), sympathy (4.03%), obligation S to O (4.03%), modesty (4.03%), feeling reticence (2.42%), and obligation O to S 4 utterances (2%).